2013
DOI: 10.1038/ki.2012.457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frequent hemodialysis on residual kidney function

Abstract: Frequent hemodialysis can alter volume status, blood pressure and the concentration of osmotically active solutes, each of which might affect residual kidney function (RKF). In the Frequent Hemodialysis Network Daily and Nocturnal Trials, we examined the effects of assignment to 6 compared to 3 times per week hemodialysis on follow up RKF. In both trials, baseline RKF was inversely correlated with number of years since onset of ESRD. In the Nocturnal Trial, 63 participants had non-zero RKF at baseline (mean ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
158
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(182 citation statements)
references
References 42 publications
6
158
0
12
Order By: Relevance
“…In our exploratory analyses, we noted that adjustment for time-updated measurements of BUN resulted in attenuation of the effect estimate for the difference in daily rate of change in urine output, supporting the notion that adjustment for BUN as a marker of solute load resulted in a smaller difference in changes in urine output between the less intensive and more intensive arms. Again, analogous evidence exists in patients on chronic HD, in whom more frequent HD (resulting in lower timeaveraged urea concentrations) has been reported to be associated with a more rapid decline in urine output (33,34).…”
Section: Discussionmentioning
confidence: 74%
“…In our exploratory analyses, we noted that adjustment for time-updated measurements of BUN resulted in attenuation of the effect estimate for the difference in daily rate of change in urine output, supporting the notion that adjustment for BUN as a marker of solute load resulted in a smaller difference in changes in urine output between the less intensive and more intensive arms. Again, analogous evidence exists in patients on chronic HD, in whom more frequent HD (resulting in lower timeaveraged urea concentrations) has been reported to be associated with a more rapid decline in urine output (33,34).…”
Section: Discussionmentioning
confidence: 74%
“…Self-reported physical health and functioning were improved but had no significant effect on objective physical performance (8). The FHN Group also reported on cardiac function (9,10), anemia (11), residual kidney function (12), and nutrition (13).…”
mentioning
confidence: 94%
“…Randomized, controlled trials of a higher dialysis dose or frequency have shown inconsistent results [7][8][9][10][11][12] and may accelerate residual kidney function (RKF) decline. 13 An incremental approach to HD initiation may offer many potential benefits to patients, including better preservation of an arteriovenous fistula, reduced cost, and preservation of RKF. Less frequent (i.e., twice weekly) HD has been associated with greater preservation of RKF after initiation of HD, [14][15][16] and higher RKF is associated with better patient survival in both PD and HD patients.…”
mentioning
confidence: 99%